2009
DOI: 10.1002/aqc.1027
|View full text |Cite
|
Sign up to set email alerts
|

Complementary use of natural and artificial wetlands by waterbirds wintering in Doñana, south‐west Spain

Abstract: ABSTRACT1. The Don˜ana wetland complex (SW Spain) holds more wintering waterfowl than any other wetland in Europe.2. This study focused on the use made by 12 common waterbirds (eight ducks and four waders) of the natural seasonal marshes in Don˜ana National Park (DNP) and the adjacent Veta la Palma (VLP) fish ponds created in the early 1990s. Data used were from aerial and terrestrial surveys collected between October and February during six consecutive winters from 1998/99 to 2003/04. Changes in distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 47 publications
2
78
0
3
Order By: Relevance
“…Veta la Palma has an important conservation role in providing feeding grounds for the large wetland bird population during the summer months when the main wetlands in the Doñana National Park are dry (Figuerola and Green 2004;Kloskowski et al 2009), and it is the existence of these reconstructed wetlands that enables a larger and more diverse waterbird community to persist (Kloskowski et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veta la Palma has an important conservation role in providing feeding grounds for the large wetland bird population during the summer months when the main wetlands in the Doñana National Park are dry (Figuerola and Green 2004;Kloskowski et al 2009), and it is the existence of these reconstructed wetlands that enables a larger and more diverse waterbird community to persist (Kloskowski et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In the 1990's, from previous agricultural land, approximately 3000 ha of wetlands were reconstructed in the form of forty large (70 ha) shallow (0.5 m) brackish-water lagoons, complete with bird shelter/nesting islands and a deeper (1 m) peripheral canal. The permanently inundated lagoons at Veta la Palma provide a vital refuge for these ducks and other waterbirds during the dry season and until winter rains re-flood the Doñana marshes bird populations in Veta la Palma can reach 300,000 (Kloskowski et al 2009). These lagoons are particularly important feeding grounds for great cormorants (Phalacrocorax carbo), greater flamingos (Phoenicopterus roseus), black winged stilts (Himantopus himantopus) and pied avocets (Recurvirostra avosetta) (Rendon et al 2008), and feeding by flamingos, coots and ducks has been shown to have a significant influence on the biomass of both macrophytes and invertebrate populations Rodriguez-Perez and Green 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Rice-paddies, created on top of the former natural marshes, are artificially flooded depending on rice cultivation needs and water available for cultivation. These areas, together with salt pans and aquaculture ponds, constitute an extensive system of artificial wetlands in the Doñana protected area that also provide refuge habitat for many species or water birds, especially when natural wetlands are dry [35].…”
Section: Study Areamentioning
confidence: 99%
“…Hydroperiod becomes a net predictor for aquatic plant species distribution, marsh primary production, and habitat characteristics. Several works have already identified the importance of the hydroperiod duration in predicting the presence, abundance, and breeding success of different waterbird species in the Doñana marshes [76][77][78][79][80][81], and also on raptors foraging in the marshes [82]. The output layers for every single date, i.e., flooding masks and hydroperiod maps per cycle, are accessible online via Web Map Services [83].…”
Section: Monitoring Flooding Regime Of Doñana Marshes: the Scientificmentioning
confidence: 99%